First record of Gasteruption Latreille (Hymenoptera: Evanioidea: Gasteruptiidae) from Fiji with the description of a new species - Parslow, Ben A.; Stevens, Mark I.; Schwarz, Michael P. (Zootaxa, 2018)
A new Gasteruption Latreille species, G. tomanivi, is described from Viti Levu, Fiji. The new species is the first record of the genus for Fiji and can be distinguished from other Oceanian Gasteruption species by the length of the mesosoma and the large malar space compared with the length of the pedicel. DNA Barcode (mtDNA—COI) sequence is provided.